2015
DOI: 10.1016/j.devcel.2014.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Cohesin Rec11/SA3 by Casein Kinase 1 Promotes Homologous Recombination by Assembling the Meiotic Chromosome Axis

Abstract: In meiosis, cohesin is required for sister chromatid cohesion, as well as meiotic chromosome axis assembly and recombination. However, mechanisms underlying the multifunctional nature of cohesin remain elusive. Here, we show that fission yeast casein kinase 1 (CK1) plays a crucial role in assembling the meiotic chromosome axis (so-called linear element: LinE) and promoting recombination. An in vitro phosphorylation screening assay identified meiotic cohesin subunit Rec11/SA3 as an excellent substrate of CK1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 61 publications
(88 reference statements)
3
74
0
Order By: Relevance
“…In addition, Red1 interacts with and requires Rec8‐cohesin for its normal chromosomal association (Panizza et al, ; Sun et al, ). From these data, it seems likely that an interaction between cohesin and Red1 is central to driving Red1 chromosomal loading (possibly via Scc3, the homolog of Psc3/Rec11, in a manner analogous to fission yeast Rec11‐Rec10 axis (Phadnis et al, ; Sakuno & Watanabe, ), although this interaction might also involve Rec8 directly (Sun et al, ). Interestingly, within budding yeast pericentromeres, Red1 and cohesin chromosomal patterns diverge: Here, Red1 levels are lower than cohesin levels (Sun et al, ).…”
Section: Control Of Meiotic Recombination Within Pericentromeresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Red1 interacts with and requires Rec8‐cohesin for its normal chromosomal association (Panizza et al, ; Sun et al, ). From these data, it seems likely that an interaction between cohesin and Red1 is central to driving Red1 chromosomal loading (possibly via Scc3, the homolog of Psc3/Rec11, in a manner analogous to fission yeast Rec11‐Rec10 axis (Phadnis et al, ; Sakuno & Watanabe, ), although this interaction might also involve Rec8 directly (Sun et al, ). Interestingly, within budding yeast pericentromeres, Red1 and cohesin chromosomal patterns diverge: Here, Red1 levels are lower than cohesin levels (Sun et al, ).…”
Section: Control Of Meiotic Recombination Within Pericentromeresmentioning
confidence: 99%
“…One protein required for this assembly is a structural protein called Red1 (in budding yeast; the homolog of Red1 in fission yeast is called Rec10; Panizza et al, 2011;Sun et al, 2015). Work in fission yeast demonstrated that an interaction between Rec11-containing cohesin and Rec10 is needed for the efficient recruitment of Rec10 to fission yeast chromosomes (Phadnis et al, 2015;Sakuno & Watanabe, 2015). Pericentromeric cohesin contains Psc3 instead of Rec11 (see above; Kitajima et al, 2003), leading to an absence of Rec10 within pericentromeres.…”
Section: Control Of Meiotic Recombination Within Pericentromeresmentioning
confidence: 99%
“…Like the SC, LinE formation requires a meiosis-specific sister chromatid cohesin complex containing Rec8 and Rec11 subunits, and phosphorylation of one of them (Rec11) by a casein kinase 1 ortholog 5, 6 . Rec8 forms filamentous structures with the chromosomes aligned in parallel from one end to the other during the horsetail stage of meiosis as observed in live cells by super-resolution structured illumination microscopy (SIM) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown how LinE subunits interact with each other and other meiotic proteins using yeast two-hybrid analysis or immunoprecipitation analysis (Loidl, 2006;Spirek et al, 2010;Miyoshi et al, 2012;Estreicher et al, 2012;Sakuno and Watanabe, 2015). We and others have shown that all LinE subunits are needed for intact LinE complex formation ( Figures 1C and S3) (Davis et al, 2008;Fowler et al, 2013).…”
Section: Line Missense Mutants Have Defective Line Structuresmentioning
confidence: 74%